DEVELOPING TOOLS FOR PEACEFUL COEXISTENCE: A QUR’ANIC PERSPECTIVE - Dr. Ahmed Al-Kubise, Dr. Zia ul Haq (Hamdard Islamicus, 2021)
This study highlights the past and potential Qur’Énic role in establishing peaceful inter-cultural interactions among nations. Today’s world has shrunk into a global village. Therefore, basing standards and protocols for peaceful coexistence according to guidelines and principles of the Holy Qur’an is appropriate, so every nation, while preserving its cultural values, may play its role in human development and ensure peaceful coexistence. In this regard, this study encompasses, points of harmony among societies, providing suggestions for formation of an organized, cultural and ideological platform from the Qur’Énic perspective. The study addresses a problem: Many people believe that Islamic civilization was influenced or affected by pre-Islamic civilizations like the Greek, Persian and Roman, therefore, Islamic civilization must have derived some principles from them. On the contrary, the Holy Qur’Én has already discussed fourteen centuries earlier, various aspects of different civilizations in detail. It mentions at various places the cosmic Sunnahs (Laws) and their impact on ancient civilizations. This research clarifies a fact, that guiding principles regarding moderation and peaceful coexistence are derived from the Holy Qur’Én and impact of these Qur’Énic teachings are clearly visible in all aspects of Islamic civilization. Therefore, this research study clarifies the Holy Qur’Én’s important role in establishing and strengthening peaceful coexistence among nations in all eras.